The Influence of the TPACK Approach (Technological Pedagogical Content Knowledge) in Curriculum Management and Learning based Kurikulum Merdeka - Rosyidah, Siti; Juharyanto, Juharyanto (Proceedings Series of Educational Studies, 2024)
Currently para Teachers are faced with generation Z students whose characteristics tend to be more open to new things, interactive communication with fast feedback, liking global issue themes, and having the ease of accessing thousands of information sources from the internet. By integrating application technology, it is hoped that the learning and assessment process will be more effective and enjoyable. However, on the other hand, the digital-based learning process has not been fully implemented. These challenges stem from teachers' lack of skills in using technological tools, technological infrastructure in schools is not evenly distributed, the condition of students who do not have adequate technological tools, and school culture is still not open to the importance of integrating technology in learning. The research aims mdescribe the application of the TPACK (Technological Pedagogical Content and Knowledge) approach in curriculum and learning management, identify factors that influence the application of the TPACK approach, and evaluate the relationship between TPACK and relevant contextual factors. This research uses the SLR (Systematic Literature Review) qualitative approach method which uses literature studies as the basis for data collection, and begins with gap analysis using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. The research results show that the application of the TPACK approach in learning has a significant influence on the successful implementation of the Merdeka Curriculum. However, there are still several obstacles such as the lack of adequate training for teachers, limited technological infrastructure, the condition of school culture and the readiness of the devices that students have at home.